Regulation on Freedom of Expression on Social Media in Indonesia and Malaysia - Najib, Ainun; Umar, Umar; Abim Bhakti; Prika Fatikasari; Aminah Nur Kauthar Binti Zawawi (Journal of Indonesian Constitutional Law, 2024)
This study aims to examine and analyse the forms of regulation of freedom of opinion in the formation of good laws in Indonesia and Malaysia and how the practice and obstacles to freedom of opinion on social media between the two. In the research method, the statutory regulatory approach (Statute Approach), analytical approach (Analytical Approach), and case approach (Case Approach) are used as aspects of normative analysis. Legal materials are collected by tracing authoritative documents related to legal issues and using the literature study method. The legal materials collected are then described descriptively by combining and comparing regulations about freedom of opinion/expression to answer the legal issues raised and reach a clear solution. The results of this study show that the existence of rules that have regulated freedom of expression/opinion for Indonesia and Malaysia is still a debate in its civil society. In Malaysia, the main challenge is the strict regulations often used to suppress freedom of expression in the interests of its constitution. In Indonesia, freedom of expression rules is considered repressive, too broad, and prone to abuse to silence public criticism in the mass media.